1992
DOI: 10.1017/s0022029900030193
|View full text |Cite
|
Sign up to set email alerts
|

Trials of a novel mastitis sensor on experimentally infected cows

Abstract: Numerous attempts to develop in-line systems for the measurement of the electrical conductivity of milk as an aid to the detection of mastitis have been described. The major technical problem of fouling of electrodes exposed to milk has been overcome in the sensor tested here by use of an inductive system of measurement. The practical application of this system in the milking parlour is reported. The novel mastitis sensor has been shown to detect incipient mastitis before there are visible signs of abnormal mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A few systems with electrical conductivity sensors installed within the cluster have been developed for use in conventional milking parlours (Lake et al 1992). Such systems have had limited appeal, however, because of the diffi culty of maintaining reliable electrical connections between the LMT and claw in the hostile environment under cows' udders during milking.…”
Section: Introductionmentioning
confidence: 99%
“…A few systems with electrical conductivity sensors installed within the cluster have been developed for use in conventional milking parlours (Lake et al 1992). Such systems have had limited appeal, however, because of the diffi culty of maintaining reliable electrical connections between the LMT and claw in the hostile environment under cows' udders during milking.…”
Section: Introductionmentioning
confidence: 99%
“…However, problems with undetected sick cows and healthy cows being classified as sick still exist, and this may be explained by an insufficient description of the trait. It has been suggested that by extracting only the high EC measurements from a milking, valuable information about EC pattern may be lost (Lake et al, 1992;Nielen et. al., 1995).…”
Section: Introductionmentioning
confidence: 99%
“…which in turn fluctuates the electrical restriction of the milk. The conductivity is an easy parameter to perceive bacteria, but it is powerfully influenced by fat percentage of the milk and mainly used to diagnose the mastitis [24]. Moreover, some pesticides are likewise mixed with milk to destroy the germs existing in milk.…”
Section: Use Of Preservativesmentioning
confidence: 99%